Entrepreneurship and Innovation: Two Main Pillars that Shake the Marketing Performance of Local Coffee Shops - Bambang Bambang (Jurnal Manajemen Bisnis Era Digital, 2025)
This study aims to analyze the influence of entrepreneurship and product innovation on the marketing performance of local coffee shops in Banda Aceh City. The background of this research is based on the increasing trend of the local coffee industry which has not been accompanied by optimal marketing and innovation strategies. The research method used a descriptive-associative quantitative approach with the population of coffee shop owners and managers and a sample of 25 respondents. Data analysis was carried out by multiple linear regression using SPSS 26.0. The results of the study show that simultaneously entrepreneurship and product innovation have a significant effect on marketing performance, with an F value of 60,024 and a significance of 0,000. However, partially, only the innovation variable had a positive and significant effect on marketing performance (sig. 0.001 < 0.05), while entrepreneurship had no significant effect (sig. 0.288 > 0.05). A determination coefficient value (R²) of 0.845 indicates that 84.5% of the variation in marketing performance is explained by both variables. This study emphasizes the importance of product innovation as a dominant factor in improving the marketing performance of local coffee shops and provides implications for business owners to strengthen creativity and adaptation to consumer trends.